2022
DOI: 10.21037/qims-21-335
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative multilayered assessment of skin lightening by photoacoustic microscopy

Abstract: Background: With the emergence of various new skin-lightening products, there is an urgent need to scientifically evaluate the efficacy and toxicology of these products, and provide scientific guidance for their use based on physiological differences between individuals. Visualized imaging methods and quantitative evaluation criteria play key roles in evaluating the efficacy of skin-lightening products. In order to quantify the changes in the multilayered morphology and endogenous components of human skin befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Each laser pulse generated an A-line signal in the imaging depth direction, and B-scan tomography image composed of continuous A-line signals was obtained by 2D transverse scanning. For the spatial resolution of the imaging system, our previous experiments showed that the PAM system has a lateral resolution of about 7 μm and an axial resolution of about 50 μm 28 , 33 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each laser pulse generated an A-line signal in the imaging depth direction, and B-scan tomography image composed of continuous A-line signals was obtained by 2D transverse scanning. For the spatial resolution of the imaging system, our previous experiments showed that the PAM system has a lateral resolution of about 7 μm and an axial resolution of about 50 μm 28 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…For the spatial resolution of the imaging system, our previous experiments showed that the PAM system has a lateral resolution of about 7 μm and an axial resolution of about 50 μm. 28,33 2.2 Data Processing and Statistical Analysis For 3D photoacoustic skin image reconstruction, each A-line signal is processed by median and filtering, then linearly projected to obtain a B-Scan image, and all B-Scan images are synthesized to display the 3D skin tissue structure. Normal 3D skin includes epidermis (stratum corneum and stratum basale), dermis, and subcutaneous tissue.…”
Section: Pam Systemmentioning
confidence: 99%
See 3 more Smart Citations